Pemberdayaan Peternakan Puyuh Kabupaten Konawe Sulawesi Tenggara Melalui Optimalisasi Potensi Limbah - Hamdan Has; Astriana Napirah; Samsul Alam Fyka (MATAPPA: Jurnal Pengabdian Kepada Masyarakat, 2021)
The purpose of society partnership program is to improve the understanding and skills of quail farmers through optimizing the processing of quail livestock waste in the form of biogas and maggot cultivation as an alternative source of animal feed. The implementation of this program is carried out in 2020 with funding from the Ministry of Education and Culture's DRPM. This Program implementation partners are Quail Farmers in Konawe District, Southeast Sulawesi Province. The methods of society partnership program are socialization of the program to partners, training in making biogas and its installation, piloting a simple biogas installation, and cultivating quail dung magots. The result of the implementation of the partnership program is that it is known that the partners' knowledge about livestock waste processing is still very low. So that in overcoming this problem, quail waste processing is carried out by means of demonstrations of making biogas and its installation which can be useful as household fuel and biogas waste as organic fertilizer. In addition, the bioconversion of quail waste into magot as animal feed is also carried out. This activity is able to provide new understanding for breeders in an effort to increase livestock business that is efficient, environmentally friendly and has economic value.